Lord Kames : legal and social theorist - Rahmatian, Andreas, 1967- (Edinburgh : Edinburgh University Press, 2016)
Andreas Rahmatian explains Kames' conceptions of legal philosophy, including black-letter law, legal science, legal theory, legal sociology, and anthropology in its early stages, setting them in the context of the Scottish Enlightenment.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 23, 2015).
Keywords: Kames, Henry Home, -- Lord, -- 1696-1782.; Law -- Philosophy; Law; Jurisprudence & general issues